The Influence Of Career Development And Work Stress On Employee Performance At The Employee Of The Service Of Population And Civil Registration (Disdukcapil) In Padang City - Feni Feni; Riri Mayliza (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine the effect of career development and work stress on employee performance at the Office of Population and Civil Registry (Disdukcapil) Padang City. This type of research is quantitative research. The sample consisted of 75 employees of the Padang City Population and Civil Registry Service (Disdukcapil) using total sampling. Data analysis used is multiple linear regression analysis, classical assumption test, and hypothesis testing. The results showed that career development and job stress variables partially had a positive and significant effect on employee performance at the Padang City Population and Civil Registry Service (Disdukcapil) employees.